Representative of Islam in Malaysian Chinese newspapers - Ahmad, Che Mahzan (s.n, 2012)
Malaysia is a multi-ethnic and multi-cultural nation. Such make up is related to the legacy arising out of long history of British colonialism over the country. Under Britsh rule, various ethnic groups were "separated" in various forms of bordering (Malays were expected to stay in villagers to be farmers, Chinese were to be shopkeepers in towns, and Indian as laborers in plantations) under the rubric of colonial pluralism